Budgeting as an Element of Planning in an Enterprise - Żaba-Nieroda, Renata (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2018)
The study presents principles of material and financial planning in a production company. An important aspect of managing a business is budgeting, which involves a set of activities performed in accordance with the rules and methods relevant to this process. Activities also mean the quantification of descriptive intentions and the means of their implementation. In addition to asserting that planning and controlling business activities on a budget basis is a must and one of the key elements of sound management, material and financial plans make it possible for a business to describe and plan its needs in a timely and transparent manner for the coming period, and to compare and summarise their costs. The article analyses practices that have been used in budgeting, designing pro-forma accounts related to the implementation of financing processes in companies’ day-to-day operations and strategic financial decisions.